The Mediating Role of Self-Esteem in the Relationship Between Self-Efficacy and Socio-Cultural Adaptation: A Case Study of AuPair Program Alumni - Prasetyono, Hendro; Nurdin, Nurdin; Pratiwi, Elisabet Yudith Dian; Ramdayana, Ira Pratiwi (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research has a purpose to determine the direct and indirect influence of self-efficacy on sociocultural adaptation through the self-esteem of Indonesian students who take part in the AuPair program in Germany. The research sample was 53 Indonesian students who had participated in the Au Pair program in Germany. Not many alumni of the Au Pair program come from Indonesia. In 5 years (2017-2022) only 53 young people from Indonesia have participated in this program. The research instrument uses a questionnaire compiled from developing indicators for each variable. Data analysis techniques use description analysis, normality test, multiple regression, correlation coefficient analysis, and hypothesis testing using the SPSS 25 application. Research results: self-efficacy can be a good predictor for sociocultural adaptation variables and self-esteem. However, self-esteem cannot be a mediating variable for self-efficacy on sociocultural adaptation. Self-efficacy and self-esteem are both independent variables that can contribute to socio-cultural adaptation. The implication is that every Indonesian student who wants to continue their studies abroad must increase their self-efficacy and self-esteem through various training or mentoring programs regarding the culture of the country they are going to and the skills needed by prospective students abroad. There needs to be further research involving a larger sample which might produce different results and analyze the factors causing why self-efficacy does not have an indirect effect on socio-cultural adaptation through self-esteem.